A study on fashion window displays in Malaysia and its influence on consumers shopping decision / Nor Aishah Zaha Zainal Abidin - Zainal Abidin, Nor Aishah Zaha (2016)
Communication in retail is a vital process for consumers to understand the message intended by retailers. Based upon this argument, the research aim is to explore how retailers can communicate better message using visual elements. In Malaysia retail industry, some shopping malls started to face deficit and failing numbers of mall tenants due to the inability to attract consumers because of unappealing shopping environments. The government's aim is to make Malaysia as famous shopping destinations and it should be utilized by all parties especially retailers, marketers and designers to attract more customers. This study uses social semiotic as the basis to examine signs utilized within window displays configurations and its effect on influence consumer's shopping decision. Analysis of data was based on semiotic analysis as their suitability on analyze visual and aids the audience to read the imbued meaning. Interviews with consumers were conducted at Suria KLCC and Pavilion KL shopping mall to find out consumer's opinions about window display designs. The results revealed that window displays in Kuala Lumpur major shopping malls applied signs effectively to create meaningful message for consumers to understand the product through pragmatic meaning, emotive meaning and functional meaning. This study also provides insights for retailers about types of window display presentation techniques that influenced consumer's shopping decision making. This study provides information why window display should be considered as important visual medium based on the findings found how window display shapes consumer's desire identity and shopping decision. Understanding the language on visual will help to reduce subjective decision making and thus improve meaning transfer between designer and consumer. It will improve level of communication skills in terms of visual literacy among society.